ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PADA KELAS XI BUDAYA DI SMAK St. FRANSISKUS ASISI LARANTUKA - Agnes Ona Bliti Puka (STKIP Weetebula, 2021)
The purpose of this study is to determine the ability to understand the mathematical concept of students of class XI Culture SMAK St. Francis of Assisi Larantuka. The data are collected by the results of students’ ability test in understanding of mathematical concepts and unstructured interviews. The test questions used to measure students’ abilities in understanding mathematical concepts consist of 2 questions in the form of descriptions with matrix transpose material and matrix multiplication. The test results are analysed based on indicators of mathematical understanding, namely: 1) the ability to explain a definition in their own words according to essential traits/characteristics, 2) the ability to make examples in mathematical concepts, 3) the ability to use concepts in solving problems. Population in this study are students on eleventh culture class of SMAK St. Francis of Assisi Larantuka with two sample of students. The results show that there are the differences in the ability to understand mathematical concepts between students through Problem Based Learning.Keywords: Mathematical concepts understanding, Problem Based Learning, matrix.